2018
DOI: 10.3847/2041-8213/aadf89
|View full text |Cite
|
Sign up to set email alerts
|

Noble Gas Abundance Ratios Indicate the Agglomeration of 67P/Churyumov–Gerasimenko from Warmed-up Ice

Abstract: The origin of cometary volatiles remains a major open question in planetary science. Comets may have either agglomerated from crystalline ices condensed in the protosolar nebula (PSN) or from amorphous ice originating from the molecular cloud and interstellar medium. Here, based on the recent argon, krypton, and xenon measurements performed by the ROSINA mass spectrometer on board the European Space Agency's Rosetta spacecraft in the coma of 67P/Churyumov-Gerasimenko, we show that these noble gas relative abun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…From the N I CO ⁄ = (5.70 ± 0.66)‰ measured early in the mission at ~3.1 au, Rubin et al (2015a) derived a formation temperature between 24 and 27 K based on laboratory measurements of the relative trapping efficiencies of N2 versus CO in amorphous water ice at different temperatures (Bar-Nun et al 2007). The case of a crystalline origin of the cometary ices, i.e., the reconfiguration of the ices in the protosolar nebula, was studied by Lectez et al (2015) and yielded a somewhat higher formation temperature of around 45 K. Taking the Ar CO ⁄ = (0.187 ± 0.091)‰ ratio into account, Mousis et al (2018) then suggested a further refined crystalline ice model requiring multiple layers of reconfigured ices. Table 2 yields N I CO ⁄ = (2.9 ± 1.2) • 10 aI in the bulk of the nucleus for the May 2015 period, which is about 5 times higher than the value derived in Rubin et al (2015a) for the October 2014 period listed above.…”
Section: Discussionmentioning
confidence: 99%
“…From the N I CO ⁄ = (5.70 ± 0.66)‰ measured early in the mission at ~3.1 au, Rubin et al (2015a) derived a formation temperature between 24 and 27 K based on laboratory measurements of the relative trapping efficiencies of N2 versus CO in amorphous water ice at different temperatures (Bar-Nun et al 2007). The case of a crystalline origin of the cometary ices, i.e., the reconfiguration of the ices in the protosolar nebula, was studied by Lectez et al (2015) and yielded a somewhat higher formation temperature of around 45 K. Taking the Ar CO ⁄ = (0.187 ± 0.091)‰ ratio into account, Mousis et al (2018) then suggested a further refined crystalline ice model requiring multiple layers of reconfigured ices. Table 2 yields N I CO ⁄ = (2.9 ± 1.2) • 10 aI in the bulk of the nucleus for the May 2015 period, which is about 5 times higher than the value derived in Rubin et al (2015a) for the October 2014 period listed above.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, measurements at comet 67P/C-G indicate deviations relative to the respective standards in the isotopic ratios of (i) oxygen 74 On the other hand, 12 C/ 13 C in CO, 16 132 Xe are all indistinguishable from their corresponding standard at the 1-σ level. Given these isotopic variations of a given element among different molecules and noticeable deviations from the solar isotopic composition, these results point to a non-homogeneously mixed protosolar nebula.…”
Section: Formation In the Dark Cold Prestellar Core -Isotopic Recordmentioning
confidence: 92%
“…Independent of the pre-or protosolar nebula origin, the radiolysis formation model predicts correlated outgassing of S 2 and H 2 S. Furthermore, the radiation also forms voids in amorphous H 2 O ice in which S 2 can accumulate and remain stable even after crystallization. This suggests a correlation also between S 2 and H 2 O (Mousis et al 2018b), while at 67P/C-G the correlation among these species was rather poor (Calmonte et al 2016).…”
Section: Sulfur Chemistrymentioning
confidence: 93%
“…Furthermore, different D/H ratios in singly versus doubly deuterated water emphasizes that isotopic equilibration in the ices of a comet are limited after its formation. To which extent D-H exchange can be inhibited in the alternative scenario of warmed-up ice agglomeration by Mousis et al (2018b) remains to be investigated.…”
Section: The Variation In D/hmentioning
confidence: 99%